European Association of Nuclear Medicine and European Academy of Neurology recommendations for the use of brain 18F‐fluorodeoxyglucose positron emission tomography in neurodegenerative cognitive impairment and dementia: Delphi consensus. (20th July 2018) - Nobili, F.; Arbizu, J.; Bouwman, F.; Drzezga, A.; Agosta, F.; Nestor, P.; Walker, Z.; Boccardi, M.; ,
Abstract : Background and purpose: Recommendations for using fluorodeoxyglucose positron emission tomography (FDG‐PET) to support the diagnosis of dementing neurodegenerative disorders are sparse and poorly structured. Methods: Twenty‐one questions on diagnostic issues and on semi‐automated analysis to assist visual reading were defined. Literature was reviewed to assess study design, risk of bias, inconsistency, imprecision, indirectness and effect size. Critical outcomes were sensitivity, specificity, accuracy, positive/negative predictive value, area under the receiver operating characteristic curve, and positive/negative likelihood ratio of FDG‐PET in detecting the target conditions. Using the Delphi method, an expert panel voted for/against the use of FDG‐PET based on published evidence and expert opinion. Results: Of the 1435 papers, 58 papers provided proper quantitative assessment of test performance. The panel agreed on recommending FDG‐PET for 14 questions: diagnosing mild cognitive impairment due to Alzheimer's disease (AD), frontotemporal lobar degeneration (FTLD) or dementia with Lewy bodies (DLB); diagnosing atypical AD and pseudo‐dementia; differentiating between AD and DLB, FTLD or vascular dementia, between DLB and FTLD, and between Parkinson's disease and progressive supranuclear palsy; suggesting underlying pathophysiology in corticobasal degeneration and progressive primary aphasia, and cortical dysfunction in Parkinson's disease; using semi‐automated assessment to assist visual reading. Panellists did not support FDG‐PET use for pre‐clinical stages of neurodegenerative disorders, for amyotrophic lateral sclerosis and Huntington disease diagnoses, and for amyotrophic lateral sclerosis or Huntington‐disease‐related cognitive decline. Conclusions: Despite limited formal evidence, panellists deemed FDG‐PET useful in the early and differential diagnosis of the main neurodegenerative disorders, and semi‐automated assessment helpful to assist visual reading. These decisions are proposed as interim recommendations. Abstract : Click here for the corresponding questions to this CME article.